Sahiwal cattle: An evaluation of their potential contribution to milk and beef production in Africa - Trail, J.C.M.; Gregory, K.E. (International Livestock Centre for Africa, 1981)
Evaluates and compares the productivity under commercial management levels of Sahiwals, Sahiwal/Ayrshire crossbreeds, indigenous Small East African Zebus and Boran, using data from 5 herds in Kenya, with particular reference to reproductive and growth characters, milk production, viability and index of cow productivity; discusses breed and environmental effects on productivity levels and the formation of composite breeds using Sahiwal cattle.